Pliable Guidance: A Multilevel Model of Curiosity, Feedback Seeking, and Feedback Giving in Creative Work - Harrison, Spencer H.; Dossinger, Karyn (Academy of Management Journal, 2017)
We propose and test a multilevel model that positions trait curiosity as a key individual difference during the revision and evaluation stages of the creative process. Using a sample of T-shirt designers, their creative drafts, and the questions and comments that feedback seekers and providers posted to an online workshop, we find curiosity acts as a bridge connecting creative workers with their feedback providers in novel ways. We advance pliable guidance as a theoretical umbrella to describe how feedback seekers and providers in creative work find a balance between the direction that makes feedback informative and the freedom to explore that infuses new ideas in their work. Our findings show that more curious individuals seek feedback by asking more open questions, which allows them to obtain more feedback. We also find that ambivalent feedback is more likely to lead to feedback acceptance and design revision. Finally, our results suggest that curiosity is an important moderator of how creative workers respond to ambivalent feedback. Our research highlights the pivotal role curiosity plays in drawing individuals into a collaborative process when developing their creative ideas, one that is guided and inspired by the social environment.